2019
DOI: 10.3390/medsci7020020
|View full text |Cite
|
Sign up to set email alerts
|

Double Burden of Malnutrition (DBM) and Anaemia under the Same Roof: A Bangladesh Perspective

Abstract: The double burden of malnutrition (DBM) and anaemia is a growing concern in developing countries. Using the cross-sectional Bangladesh Demographic Health Survey, 2011, 5763 mother–child pairs were examined. In households where the mother was overweight, 24.5% of children were stunted, 19.8% underweight, 9.3% wasted, and 51.7% anaemic. Significant regional differences were found in DBM and anaemia as well as drinking water source, while DBM alone was more common in more well-off households (based on wealth inde… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
19
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 34 publications
5
19
1
Order By: Relevance
“…A higher rate of TBM than DBM could be a result of the fact that more than than half (53%) of the children aged 6-59 months were found to be anemic in Nepal in the NDHS [13]. Mamun et al (2019) also found the prevalence of overweight mothers with anemic children to be 27% in Bangladesh. TBM prevalence is higher, perhaps dueto the higher prevalence of anemia among children aged less than 59 months in developing countries including Nepal.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A higher rate of TBM than DBM could be a result of the fact that more than than half (53%) of the children aged 6-59 months were found to be anemic in Nepal in the NDHS [13]. Mamun et al (2019) also found the prevalence of overweight mothers with anemic children to be 27% in Bangladesh. TBM prevalence is higher, perhaps dueto the higher prevalence of anemia among children aged less than 59 months in developing countries including Nepal.…”
Section: Discussionmentioning
confidence: 99%
“…Despite declining undernutrition among children, micronutrient deficiency anemia remains one of the intractable public health problems in South Asia [39]. Despite limited evidence available so far on TBM, maternal overweight/obesity is a crucial factor contributing to child anemia [1]. The plausible mechanism for the phenomenon of TBM has not been examined clearly.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study shows that the prevalence of TBM among mother-child pairs was 7.00 % in Nepal [46]. Despite limited evidence available so far on TBM, maternal overweight/obesity is a crucial factor contributing to child anemia [1]. The plausible mechanism for the phenomenon of TBM has not been examined clearly.…”
Section: Discussionmentioning
confidence: 68%
“…The various forms of malnutrition among children and mothers are significant public health challenges in low-and middle-income countries [1]. Various forms of malnutrition contribute to the double and triple burden of malnutrition.…”
Section: Introductionmentioning
confidence: 99%